Distribusi Serapan Sayur Paprika pada Rantai Pasok di Kecamatan Baturiti Hingga Ke Konsumen - IGusti Ayu Indah Kusuma Dewi; I Gusti Ngurah Apriadi Aviantara; I Wayan Widia (Jurnal BETA (Biosistem dan Teknik Pertanian), 2020)
This study aimed to determine the marketing distribution channel and analyze the absorption of paprika from the farmer in Baturiti district to the last costumers and calculate the marketing margins obtained in each distribution channel. This research was conducted in July-August 2018. This study used purposive sampling survey. There are five distribution channels of paprika from the farmers in Baturiti regency to the last costumers namely: 1st line (Farmers → Traditional Markets → Consumers), 2nd line (Farmers →Collectors → Suppliers → Consumers), 3rd line (Farmers → Collectors → Suppliers → Costumers), 4th line (Farmers → Collectors → Consumers), 5th line (Farmers → Suppliers → Consumers). The distribution shows that the market level of paprika and farmers’ production is 2655 monthly. The absorption of paprika distributed by farmers to collectors, suppliers, and traditional markets are 25.6 percent, 38.8 percent, and 35.6 percent. Paprika that is distributed by collectors to suppliers andtraditional markets are 19.6 percent and 6 percent. Suppliers obtain 58.4 percent paprika for farmers and is distributed to hotel or restaurant, supermarket and traditional markets each at 29.8 percent, 21.5 percent, and 7.1 percent. Based on the five channels obtained in this study, line III is the longest distribution channel, and lines III and V produce the highest marketing margins and profit margins. While line I is the shortest distribution channel and has the lowest marketing margins and profits. This is because the marketing costs incurred are small and the selling price at the last consumer level is also the lowest compared to the other five channels